Vertebral metrics: application of a mechanical instrument to evaluate the spinal column in pregnant women - Quaresma, Cláudia (2013)
The published literature about the biomechanical alterations of the spinal column during pregnancy is scarce and disperses, being more qualitative and limited to partial analysis of the spinal column. The main justification for a global approach to be neglected could be related to the inexistence of a non-invasive instrument that evaluates the spinal column in an objective and complete way. Thus, in order to fill this gap, we built Vertebral Metrics - a device that allows the identification of the 3D position of the vertex of each of the spinal processes, from the first cervical vertebra to the first sacral vertebra and calculate the amplitude of the angles of curvature of the spinal column in the standing position. The present work has the objective of presenting the first application of this equipment to 49 pregnant women at four different moments of pregnancy (12, 20, 32 e 37 weeks of gestation). Analysing the results we can conclude that Vertebral Metrics - is an innovative instrument in the global evaluation of the spinal column in a standing position, allowing a quantitative analysis of its shape and temporal variations